Capital Market Equilibrium and Annual Accounting Numbers: Empirical Evidence - Gonedes, Nicholas J. (Journal of Accounting Research, 1974)
Information Content of accounting numbers, Financial Ratios, Asset pricing, Two-Parameter asset pricing model